Aceclofenac-loaded pluronic F108/L81 mixed polymeric micelles: effect of HLB on solubilization - M. Senthilkumar; Sasmita Dash; R. Vigneshwari; E. Paulraj (Designed Monomers and Polymers, 2022)
Pluronic block copolymers have phase behavioural characteristics which are extensively studied for drug delivery applications. In this study, we explored hydrophilic pluronic F108 (HLB = 27), hydrophobic pluronic L81 (HLB = 2) and their mixed micelles acting as solubilising mediums for model drug aceclofenac. The drug solubilisation and interactions have been analysed using UV-visible spectroscopy, Fluorescence spectroscopy, Rheology studies, Fourier-transform infrared spectroscopy, Scanning electron microscope, Dynamic light scattering, Cloud point and partition coefficient measurements. The investigation from UV-spectrophotometry demonstrated that mixed pluronic entrapped greater number of aceclofenac molecules than both the neat pluronics at same concentration. Excimer formation was evidenced from fluorescence spectra with pyrene as a probe. The rheological studies showed difference in viscosity over low shear range. Studies on FTIR demonstrated probable bonding between the aceclofenac and mixed pluronic molecules. The DLS studies on mixed pluronic showed swelling of micellar diameter from 317.6 nm to 413.5 nm. Thermodynamic parameters of the above system revealed higher partition coefficient value for mixed pluronic and spontaneity in drug solubilisation. This study can be exploited to use a hydrophobic copolymeric micelle in mixed pluronic formulation for better drug solubilisation.